Health Communication in Media: An Analytical Study of Coverage of World Blood Donor Day in Leading National Dailies from Jaipur - Pandey, Hemant Kumar; Kumar, Subhash; Dixit, Prabhat (Indian Journal of Community Health, 2021)
As we know Print media is known for its credibility. It is believed that whatever is published in newspapers is true and authentic. Newspapers have a wide reach and huge readership and it can be said that campaigning with mass media like newspapers are associated with many benefits. Firstly it can reach a large number of people. Secondly, it is considered to be a credible source of information. Thirdly through the newspapers the readers can be reminded about the issues at hand their beliefs reinforced on regular basis. Newspapers have a large readership throughout the world. They can contribute maximally to health education awareness of people by publishing articles on health related issues. Global daily circulation of newspaper was 5.19 million having a readership of 2.3 billion in 2010. This was 20% more than the internet users worldwide. In the age of internet still newspapers are relevant and represent 8% of total media consumption time (https://www.journalism.org/fact-sheet/newspapers/). In India Registered newspapers are 82,237 and Hindi language newspapers are leading the race followed by English and other regional languages. Thus, we can say that Newspapers are very important tool to disseminate health education among people and it can bring change in society. (http://rni.nic.in/)